2016
DOI: 10.1002/wmh3.190
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Food Markets, NGOs, and Health Policy: Improving Food Access and Food Security, Trust Bonds, and Social Network Ties

Abstract: Limited access to healthy foods in low‐income areas is well documented as part of “the new hunger” in the United States. Characterized by easy access to nutrient‐poor processed food and blocked access to foods that secure dietary health and sustain well‐being, “the new hunger” has been linked in public health and social science literature to obesogenic environments, defined as both food and built environments that promote obesity. The paper examines how non‐governmental organizations work within distinct polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Patil and colleagues () have also suggested that social support and community integration among resettled refugees may provide access to important information regarding food; for example, where to locate traditional foods. Observing a similar initiative to the FJT (a mobile produce market for low‐income consumers) in the USA, Best and Johnson () found that social ties between staff and customers were an important part of providing a service free from shame or stigma. Previous research in Melbourne has also documented the importance of social opportunities in food insecurity interventions (Allen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patil and colleagues () have also suggested that social support and community integration among resettled refugees may provide access to important information regarding food; for example, where to locate traditional foods. Observing a similar initiative to the FJT (a mobile produce market for low‐income consumers) in the USA, Best and Johnson () found that social ties between staff and customers were an important part of providing a service free from shame or stigma. Previous research in Melbourne has also documented the importance of social opportunities in food insecurity interventions (Allen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of rising need, limited resources, and inadequate government support, some nongovernment organisations are pursuing new methods of addressing food insecurity. These initiatives range from community supported agriculture programmes (Miewald, Holben, & Hall, ) to local food hubs (Levkoe & Wakefield, ) and mobile produce markets that visit low‐income neighbourhoods (Best & Johnson, ). These approaches attempt to provide alternatives to traditional food aid in a way that is both financially sustainable and less stigmatising and are increasingly operating under social enterprise models (business that exist to achieve social outcomes).…”
Section: Introductionmentioning
confidence: 99%
“…Other social enterprises working to alleviate food insecurity within the USA and Australia have demonstrated this capacity to increase social connection and provide an environment that can be free of shame or stigma with customers returning for social benefits such as community and societal acceptance and inclusion. Customers are treated with dignity and begin to make friends [ 25 , 54 ]. The current study found some people who are seeking asylum were using the FJT as a social space where friendships could be cultivated among asylum seekers, staff, and volunteers especially between individuals with proficiency in a common language.…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood level social cohesion and trust, the social capital residents possess, have been shown to mitigate food insecurity type and severity (Best and Johnson 2016 ; Martin et al 2004 ; Leddy et al 2020 ). Investigating a high-impact mobile farmers market program that served low-income residents in D.C.’s Wards 7 and 8, Best and Johnson ( 2016 ), for example, found reciprocal social networks were an effective resource that community organizations, in partnership with community stakeholders, could leverage to improve food access. They apply Granovetter’s ( 1973 ) seminal “strength of weak ties” thesis to capture the unifying power of weak ties (ties between people we sort of know) that function as a bridge to others and enable broad diffusion of information across groups.…”
Section: Introductionmentioning
confidence: 99%
“…They apply Granovetter’s ( 1973 ) seminal “strength of weak ties” thesis to capture the unifying power of weak ties (ties between people we sort of know) that function as a bridge to others and enable broad diffusion of information across groups. Best and Johnson ( 2016 ) document how the formation of weak ties between staff and customers through market exchanges that centered dignity and respect, combined with organizational networks with local institutions which function as social infrastructure, like churches and local community groups, facilitated trust bonds. These bonds, in turn, spurred word-of-mouth outreach by customers, thereby expanding the mobile market’s reach, which itself became part of the community’s sustaining social infrastructure.…”
Section: Introductionmentioning
confidence: 99%